ЎЗБЕКИСТОНДА ШИРКАТ ХЎЖАЛИКЛАРИДАГИ МУАММОЛАР ВА УЛАРНИНГ ТУГАТИЛИШИ (Scientific journal of the Fergana State University, 2023)
In this article the activity of mutual household which  functioning in the sector of agriculture of Uzbekistan in the period of  Independence are analysed.  Also, the problems of mutual  households` as well as  matters connected with applying sanitation regarding unprofitable mutual household  and their  elimination are considered.